The birth of autobiographical self. Mácha’s personal diary and modern poetic diaries towards the Romantic idea of subjectivism - Marciniak, Hanna (Poznańskie Studia Slawistyczne, 2011)
My text is an attempt to apply Charles Taylor’s theory, dealing with the origins of the modern self, to Czech autobiographical literature originating in Romanticism. Taking a cue from Jean Starobinski and Philippe Lejeune’s concepts of modern autobiography, I analyse Karel Hynek Mácha’s personal diary from 1835 and try to find and emphasize its narrative and compositional aspects, which anticipate the poetics of modern poetic diaries.